(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2022)
Biosurfactants are structurally diverse surface-active agents mostly produced by various genera of bacteria, yeast and filamentous fungi that have a wide range of applications and properties. They have surface and interfacial activity, temperature and pH tolerance, biodegradability, low toxicity and anti-adhesive property. Their production was reported to be affected by temperature, PH, aeration and agitation, salt concentration and carbon and nitrogen sources. Bacteria species of the genera Acinetobacter, Arthrobacter, Agrobacterium, Antarctobacter, Bacillus, Clostridium, Lactobacillus, Halomonas, Serratia, Rhodococcus and filamentous fungi of the genera Aspergillus, penicillium, and yeast like Candida, Yarrowia, Torulopsis, Pseudozyma, Saccharomyces were the most notable biosurfactant producing microorganisms. Surfactin, lichenysin, rhamnolipid, Sapporolipid, liposan, viscosin, alasan, and subtilisin were among the most produced biosurfactants. The need to expand knowledge of physiology, genetics and biochemistry of biosurfactant-producing strains and the development of the process technology will help to reduce production costs.